Proceedings of the 6th International Workshop on SHAring and Reusing Architectural Knowledge 2011
DOI: 10.1145/1988676.1988687
|View full text |Cite
|
Sign up to set email alerts
|

Using code analysis tools for architectural conformance checking

Abstract: Architectural conformance checking verifies whether a system conforms to its intended architecture, which is essential to safeguard the quality attributes of the system. Due to the size of many systems, performing conformance checking by means of manual code inspections is often practically infeasible. Code analysis tools can be used to automatically check architectural conformance.In this paper, we investigate several code analysis tools that offer support for Java and compare them on their usefulness for arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…Although ACC-tools predominantly check for the same kind of inconsistencies between the implemented and intended modular architecture, only a few studies have compared these tools. Previous studies have identified large differences in terminology and approach [3,5,6]. For instance, the study of Passos et al [5] identified and evaluated three techniques of static architecture checking.…”
Section: Introductionmentioning
confidence: 99%
“…Although ACC-tools predominantly check for the same kind of inconsistencies between the implemented and intended modular architecture, only a few studies have compared these tools. Previous studies have identified large differences in terminology and approach [3,5,6]. For instance, the study of Passos et al [5] identified and evaluated three techniques of static architecture checking.…”
Section: Introductionmentioning
confidence: 99%
“…When developers mistakenly violate these decisions, this leads to the software architecture erosion phenomenon. This gap between implementation and architecture causes the system to fail to satisfy some of the intended nonfunctional properties [14].…”
Section: Architectural Conformance Checkingmentioning
confidence: 99%
“…One further strategy to cope with architecture erosion is to use query languages [18]. Queries can be executed on the source code or other relevant artifacts to, e.g., identify all classes that depend on particular other classes or packages [17]. Thus, to assess the architectural consistency, queries need to be written that identify forbidden dependencies.…”
Section: Related Workmentioning
confidence: 99%